Rabson-Mendenhall syndrome presented as severe acanthosis nigricans in an infant harboring novel mutations in the INSR gene: a case report - Shi Yan; Yu Sheng; Hai-zhen Hui; Chun-yan Zhou; De-ming Liu (Frontiers in Pediatrics)
BackgroundRabson-Mendenhall Syndrome (RMS), a rare hereditary form of insulin resistance, is marked by severe hyperinsulinemia and early-onset acanthosis nigricans (AN) during childhood.Case presentationA case of a 15-month-old girl was reported, presenting with widespread acanthosis nigricans, growth retardation, dysmorphic facial features, and hypertrichosis. Laboratory results indicated fasting hypoglycemia and hyperinsulinemia, while her oral glucose tolerance test (OGTT) remained normal. Whole-exome sequencing revealed two novel mutations in the insulin receptor gene (INSR): a c.3392 C > G missense/frameshift mutation in exon 19 and a c.4007_4010delAGAG deletion in exon 22.ConclusionAcanthosis nigricans (AN) can serve as a clinical marker that strongly suggests underlying metabolic syndromes, making genetic analysis essential for confirming the diagnosis.